2014
DOI: 10.1097/coh.0000000000000018
|View full text |Cite
|
Sign up to set email alerts
|

Will expanded ART use reduce the burden of HIV-associated chronic lung disease?

Abstract: Purpose of Review The pulmonary complications of chronic HIV infection have shifted from infectious complications towards non-infectious pulmonary complications, predominantly chronic obstructive pulmonary disease (COPD). While the best-established COPD risk factor is cigarette smoking, emerging data suggest HIV infection also independently increases COPD risk. The purpose of this article is to review these data and the conflicting data regarding the role of antiretroviral therapy (ART) in modifying COPD risk.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 45 publications
1
23
0
Order By: Relevance
“…The same authors also reported that higher CD4 counts and undetectable viral loads were protective factors for CAP in the multivariate analysis, as were pneumococcal and influenza vaccinations. Despite effective ART, bacterial CAP is still frequent in HIV-A c c e p t e d M a n u s c r i p t infected patients (17,18), and mortality rates may be rising due to the prevalence of comorbidities in CAP patients (19). A prospective study(7) analyzing more than 18,000 patients in 34 countries over the period 2006 to 2011 reported a pneumonia incidence of 0.53 cases/100 person-years.…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…The same authors also reported that higher CD4 counts and undetectable viral loads were protective factors for CAP in the multivariate analysis, as were pneumococcal and influenza vaccinations. Despite effective ART, bacterial CAP is still frequent in HIV-A c c e p t e d M a n u s c r i p t infected patients (17,18), and mortality rates may be rising due to the prevalence of comorbidities in CAP patients (19). A prospective study(7) analyzing more than 18,000 patients in 34 countries over the period 2006 to 2011 reported a pneumonia incidence of 0.53 cases/100 person-years.…”
Section: Epidemiologymentioning
confidence: 99%
“…We recommend that such patients do not need treatment, admission, or care sites that differs from that of the general population. 13,14,15,17,18,19,20,22,23,24,25,27,28,29,30,62,63,66,67,68,70,71 A c c e p t e d M a n u s c r i p t…”
Section: Five-year Viewmentioning
confidence: 99%
“…With the advent of ART and the improvement of the immune status in patients receiving ART, infectious complications of AIDS are now better controlled. Currently, noninfectious lung diseases, like chronic obstructive pulmonary disease (COPD), are emerging as key clinical conditions [ 85 ].…”
Section: Use Of Nhps To Model Respiratory Comorbiditiesmentioning
confidence: 99%
“…Even in the modern ART era, persons with HIV are at a greater risk of developing both infectious and noninfectious pulmonary diseases than persons without HIV. For example, persons with HIV infection are at elevated risk for invasive Streptococcal pneumoniae infection, as well as chronic obstructive pulmonary disease (COPD) 5,6 . Furthermore, coinfection of tuberculosis (TB) and HIV is a significant public health challenge in certain regions of the world, notably, sub-Saharan Africa, as HIV-infected individuals are 16 to 27 times more likely to have TB than persons without HIV 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Although some explanations for this susceptibility to pulmonary infection and chronic disease have been proposed 8,9,10 , the precise cellular mechanisms by which individuals with suppressed HIV plasma viral load remain at higher risk for pulmonary complications have not been fully elucidated. Importantly, HIV is a very strong risk factor for pulmonary infection and chronic disease, independent of smoking status 6 .…”
Section: Introductionmentioning
confidence: 99%